Implications of lysyl oxidase-like protein 3 expression in the periodontium of diabetic rats (Journal of Applied Oral Science, 2022)
Objectives: Diabetes has been strongly associated with periodontal diseases. The periodontal ligament (PDL) has an abundant extracellular matrix (ECM). Lysyl oxidases (LOXs) are closely associated with various diseases caused by abnormal ECM functions, however, the role of LOXs in periodontal diseases induced by diabetes remains unclear. Methodology: In this study, 8-week-old Zucker diabetic fatty rats were used to establish a type 2 diabetes mellitus (T2DM) model. After 9 and 16 weeks, hematoxylin and eosin (H&E), Masson’s trichrome, and immunohistochemical staining were performed. Results:After 9 weeks, loose collagen fibers were found in the interradicular area of the diabetic group, in opposition to the control group. There were no significant differences in LOX expression between the diabetic and control groups (p>0.05). However, after 16 weeks, the diabetic group presented a disordered arrangement of the PDL, showing decreased collagen content and significantly increased lysyl oxidase-like protein 3 (LOXL3) expression when compared with the control group (p<0.05). This suggests that LOXL3 plays a significant role in periodontal histopathological changes in diabetic rats. Conclusion:Our study showed elevated LOXL3 expression in the PDL of diabetic rats after 16 weeks, suggesting that LOXL3 may be involved in the occurrence and development of periodontal histopathological changes in diabetic rats. LOXL3 could be further used as an indicator for the early diagnosis of diabetic periodontitis in T2DM patients in clinical settings.